Money, Marriage, and Madness : The Life of Anna Ott - Nielsen, Kim E. (Book collections on Project MUSE., 2020)
"Anna Ott died in the Wisconsin State Hospital for the Insane in 1893. She had enjoyed status and financial success first as a physician's wife and then as the only female doctor in Madison. Throughout her first marriage, attempts to divorce her abusive second husband, and twenty years of institutionalization, Ott determinedly shaped her own life. Kim E. Nielsen explores a life at once irregular and unexceptional, revealing a woman whose whiteness and privileged place in society still failed to protect her. Historical and institutional structures, like laws that liberalized divorce and women's ability to control their property, opened up uncommon possibilities for Ott. Other structures, from domestic violence in the home to rampant sexism and ableism outside of it, remained a part of even affluent women's lives. Money, Marriage, and Madness tells a forgotten story of how the legal and medical cultures of the time shaped one woman-and what her life tells us about power and society in nineteenth century America"--